2022
DOI: 10.1021/acs.energyfuels.2c01464
|View full text |Cite
|
Sign up to set email alerts
|

A New Empirical Model to Predict Methane Adsorption Amount of Anthracite Considering Temperature Effect

Abstract: Geo-temperature is a key geological parameter for coalbed methane (CBM) recovery. Especially for deep CBM, the impact of temperature on methane adsorption of coal should receive more emphasis. In this study, the methane adsorption performances of three anthracite coal samples from Shanxi Province, China, under different temperature and gas pressure conditions (20–60 °C, 1–10 MPa) are simulated based on the grand canonical Monte Carlo (GCMC) method. The results show that the Dubinin-Astakhov (DA) model has a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…3.2.2 Analysis of the influence of temperature on initial adsorption amount of gas Wang et al (2016); ; (Chen et al, 1995); (Zhong et al, 2002); ; (Liu et al, 2012); (Cai et al, 2019); (Wang et al, 2022) and others found that the amount of gas adsorption gradually decreased with the increase of temperature. It is generally accepted that the adsorption amount decreases by 8% for a 1 °C temperature increase.…”
Section: Analysis Of the Influence Of Temperature On Gas Diffusion Ratementioning
confidence: 99%
“…3.2.2 Analysis of the influence of temperature on initial adsorption amount of gas Wang et al (2016); ; (Chen et al, 1995); (Zhong et al, 2002); ; (Liu et al, 2012); (Cai et al, 2019); (Wang et al, 2022) and others found that the amount of gas adsorption gradually decreased with the increase of temperature. It is generally accepted that the adsorption amount decreases by 8% for a 1 °C temperature increase.…”
Section: Analysis Of the Influence Of Temperature On Gas Diffusion Ratementioning
confidence: 99%
“…37 Its expression is simple and exhibits good fitting effects for methane adsorption data, making it one of the most widely used models for describing methane adsorption behavior. 34,36 The L-F model, an improvement over the Langmuir model, represents a gas monolayer adsorption model that accounts for the surface heterogeneity of the adsorbent. 30,38 The BET model demonstrates good applicability in the adsorption on nonporous or mesoporous solid surfaces, describing multilayer adsorption of molecules on solid surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…32,35 The D−A model is a semiempirical formula that establishes a functional relationship between adsorption potential and the volume of the adsorption layer, based on the pore filling theory. 34,39 Undoubtedly, these models have significantly contributed to the study of the adsorption behavior in coalbed methane. However, they still exhibit certain limitations in describing methane adsorption in deep coal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation